Analysis of microglial BDNF function and expression in the motor cortex - Honey, Diana; Wosnitzka, Erin; Klann, Eric; Weinhard, Laetitia (Frontiers in Cellular Neuroscience, 2022)
Brain-derived neurotrophic factor (BDNF) is a neurotrophin that regulates several aspects of brain function. Although numerous studies have demonstrated the expression and function of BDNF in neurons, its expression in microglia remains controversial. Using a combination of genetic tools and fluorescence imaging, we analyzed BDNF expression patterns and investigated the effect of microglial Bdnf deletion on neuronal activity, early-stage spine formation, and microglia-neuron attraction in the motor cortex. We did not detect BDNF expression in microglia at the transcriptional or translational level, in physiological or pathological conditions, and none of the assessed neuronal functions were found to be affected in conditional Bdnf knockout mice. Our results suggest that microglia do not express BDNF in sufficient amounts to modulate neuronal function.